Pelatihan Penggunaan Media 3 Dimensi dalam Pembelajaran Biologi bagi Siswa Tunagrahita di Kota Tasikmalaya - Purwati Kuswarini Suprapto; Diki Muhamad Chaidir (Universitas Mathla'ul Anwar Banten, 2020)
TRAINING ON 3-DIMENSIONAL MEDIA USAGE IN BIOLOGICAL LEARNING FOR MENTALLY RETARDATION STUDENTS IN TASIKMALAYA. All students have the right to get knowledge that is beneficial in facing various challenges in a community life, no matter how many students. Biological learning done for students of disabled sought to bridge the limitations and barriers that children have and develop the potential of children in order to carry out opportunities for broader life. Through a 3-dimensional media-based learning is expected to provide understanding and skills for students who later can have creative thinking skills. In addition to the 3-dimensional media is also expected to be found several children who have potential in terms of art especially fine art. Based on the results of observations and trainings that have been done, the students are happy and have their own interest in learning to use the 3-dimensional media, but to further develop the thinking skills of students need Continuous effort. The use of 3-dimensional media can also be the basis in the training of manufacturing various products such as in the manufacture of cakes and also some artwork that has its own economic value.